Pemberdayaan Karang Taruna Putra Jaya Intan di Bidang Pendidikan, Kewirausahaan, dan Olahraga - Maulana, Maulana; Nugraha, Dadan; Ridwan, Heri (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Karang Taruna is an organization formed by the community as a forum for the younger generation to develop themselves, grow, and develop on the basis of awareness and social responsibility of younger generation, which is oriented towards achieving social welfare for the community. Karang Taruna empowerment is a process of developing capabilities, opportunities, and granting authority to Karang Taruna to increase potential, prevent and handle social problems, develop pioneering values through the use of human resources, natural-social resources, and technology. This empowerment is also felt by the Karang Taruna